HIGH SCHOOL SUCCESSFUL DEBATERS’ SELF REGULATED LEARNING STRATEGIES AT SMAN 3 MALANG - Fachrial Saputra; Ive Emalina (Universitas Jambi, 2016)
Debate is one of teaching strategies that is used in learning speaking. Debate includes the discipline of learners to manage their own learning. When learning English through debate, learners are using Self Regulated Learning (SRL) strategies. SRL strategies in debate are helping so many debaters to maintain their speaking using English as well as to think analytically while speaking using English. Therefore, this research was conducted to see the way that senior high school debaters used SRL strategies. This study used case study that is very popular form of qualitative analysis and involves a careful and complete observation of a social unit, be that unit a person, a family, an institution, a cultural group or even the entire community. Case study in this study was applied to analyze the kinds of SRL strategies that were used by senior high school successful debaters in SMA Negeri 3 Malang. This study revealed the presence and the way SRL strategies were used by the participants that were included into several attributes, including metacognitive, strategy, adapting, engaging, and self-initiating. Each of attribute was having their actions, including goal setting and planning, organizing and transforming, keeping records and monitoring, seeking social assistance, reviewing records, environmental structuring, self-evaluation, rehearsing and memorizing, self-consequence, and seeking information. Moreover, not all of the strategies always appeared on every participant and also the way that the participants used the strategies was different one to another.